Determination of Anthocyanin Content and Antioxidant Activity in Sidenuk Black Rice Mutant (Oryza sativa var. sidenuk) - Respati, Aditya Nugraha; Sumaryati Syukur; Ishak; Jamsari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2025)
The Sidenuk black rice mutant is the latest development of Sidenuk Rice which is known to excel in high rice production and is resistant to pests. Due to the many health benefits offered by black rice and no data on anthocyanin content and antioxidant activity of the mutant black rice variety Sidenuk, further research is needed. This study aims to analyze the anthocyanin content and antioxidant activity of Sidenuk black rice mutants (Oryza sativa var. sidenuk). The yield of concentrated macerate of Sidenuk black rice mutant produced was 23.25%. Based on the results obtained in the qualitative test and information from the journal, it indicates that Sidenuk black rice mutant contains anthocyanin compounds, but not in Sidenuk white rice mutant. The cyanidin 3-glucoside compound was the most abundant anthocyanin compound in the Sidenuk black rice mutant, followed by peonidin-3-glucoside. The total anthocyanin content in black rice is 1.07 ± 0.04 mg/g. This data is higher than black glutinous rice but lower than other black rice varieties. The IC50 value of Sidenuk black rice mutant is 36.02±5.09 µg/mL, which is classified as strong antioxidant and is the strongest of all black rice varieties in this study.